Effect of combined treatment of radiation and tissue-specific recombinant oncolytic adenovirus on bladder cancer cells. (1st February 2017) - Zhang, Hongjuan; Wang, Fang; Mao, Chunjie; Zhang, Zuncheng; Fu, Shengjun; Lu, Jianzhong; Zhai, Zhenxing; Li, Renju; Li, Shuwen; Rodriguez, Ron; Wang, Zhiping
Abstract: Purpose: Gene therapy combined with radiation has shown promising potential for the treatment of tumors. This paper aimed to clarify the synergistic effect of radiotherapy combined with the bladder cancer tissue-specific oncolytic adenovirus (Ad-PSCAE-UPII-E1A) on bladder cancer cells and to study the underlying synergy mechanisms of the combined treatment. Materials and methods: The Adenovirus carrying E1A under control of UPII promoter and prostate stem cell antigen enhancer (PSCAE) were successfully constructed. The viability of bladder cancer cells BIU-87 and EJ was determined by MTT assay. The apoptotic assay was demonstrated by flow cytometry and TEM. Virus titer was determined by TCID50 assay, and proteins Mre11, Chk2-Thr68, and E1A were analyzed by Western blot method. Results: Oncolytic adenovirus combined with radiotherapy improved antitumor efficacy compared with the single treatment at a time and was X-ray dosage-dependent. When the adenovirus infection was scheduled at 24 h after irradiation, cancer cells had the lowest viability. Adenovirus and irradiation induced cell death through the caspase-3 related apoptotic pathway, and bladder cancer cells were arrested at the G1 (BIU-87) or S phase (EJ). Autophagic vacuoles were observed in bladder cancer cells treated with radiation and adenovirus. After irradiation, more virus particles were observed in the BIU-87 and EJ cells. However, by a TCID50 assay, there was no difference in virus titter between irradiated bladder cancer cells and unirradiated cells. The proteins Mre11, Chk2-Thr68 which involved in the DNA break repair pathway were decreased while γ-H2AX-Ser139 increased; at the same time, the E1A gene and the hexon proteins of oncolytic adenovirus were increased after irradiation. Conclusions: Our results proved synergistic antitumor effect of adenovirus Ad-PSCAE-UPII-E1A and radiation, which might be a potential therapeutic strategy for bladder cancer.